Analyses of nano-crystalline LiCoVO4 prepared by solvothermal reaction - Thongtem T. (2014)
LiOH·H2O, Co(NO3)2·6H2O and NH4VO3 were used to prepare nano-crystalline LiCoVO4 by 150 °C solvothermal reaction in isopropanol for 10-360 h and subsequent calcination at 300-500 °C for 6 h. XRD, TEM and selected area electron diffraction (SAED) revealed the presence of nano-crystalline LiCoVO4 with inverse spinel structure. The V-O stretching vibration modes of VO4 tetrahedrons were detected by FTIR over the range 617-835 cm- 1 and by Raman spectrometer at 805.7 and 783.1 cm- 1. Co, V and O were detected by EDX. TGA of solvothermal products shows weight loss due to the evaporation and decomposition processes at 40-648 °C. © 2006 Elsevier B.V. All rights reserved.